2019
DOI: 10.3390/app9061207
|View full text |Cite
|
Sign up to set email alerts
|

MedChain: Efficient Healthcare Data Sharing via Blockchain

Abstract: Healthcare information exchange is an important research topic, which can benefit both healthcare providers and patients. In healthcare data sharing, many cloud-based solutions have been proposed, but the trustworthiness of a third-party cloud service is questionable. Recently, blockchain has been introduced in healthcare record sharing, which does not rely on trusting a third party. However, existing approaches only focus on the records collected from medical examination. They are not efficient in sharing dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
171
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(178 citation statements)
references
References 41 publications
0
171
0
7
Order By: Relevance
“…The experimental results showed that the scheme is practical and feasible for patients and medical staff, and can be applied to location information protection in telecare information systems [72]. Shen et al [73] proposed MedChain, an efficient session-based healthcare data sharing based on blockchain. MedChain uses a digest chain structure approach to check the integrity of a shared medical IoT data stream.…”
Section: Global Scientific Data Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results showed that the scheme is practical and feasible for patients and medical staff, and can be applied to location information protection in telecare information systems [72]. Shen et al [73] proposed MedChain, an efficient session-based healthcare data sharing based on blockchain. MedChain uses a digest chain structure approach to check the integrity of a shared medical IoT data stream.…”
Section: Global Scientific Data Sharingmentioning
confidence: 99%
“…This is done to overcome the efficiency issues of existing systems such as Medrec [56] and MedBlock [71]. The evaluation results show that MedChain can achieve higher efficiency and satisfy the security requirements of healthcare data sharing [73].…”
Section: Global Scientific Data Sharingmentioning
confidence: 99%
“…While the development of new drugs involves substantial costs related to studies to evaluate the safety and updating of the drug, the use of smart contracts guarantees informed consent procedures and allows in certifying the quality of data [18]. An efficient data-sharing scheme, called MedChain is proposed in [19]. It combines Blockchain, digest chain and structured P2P network techniques to overcome the efficiency issues in healthcare data sharing.…”
Section: Related Workmentioning
confidence: 99%
“…MedChain [88] is a data sharing scheme that incorporates blockchains, digest chain and structure peer-to-peer network to overcome efficiency related to metadata change when sharing data between different entities. This approach checks the integrity of shared medical IoT data stream using digest chain structure.…”
Section: Data Sharing Network/systemmentioning
confidence: 99%